The Effect of The TGT (Teams Games Tournament) Learning Model Assisted by Kahoot on Improving Students' Learning Outcomes - Lalu Salman Alfarizi; Siti Nurhidayati (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
Students' low learning outcomes are partly attributable to efforts to improve instructional quality that have not yet been implemented optimally. A range of improvement strategies can be undertaken, including curriculum renewal, enhancement of the teaching–learning process, teacher professional development, provision of learning facilities, and refinement of assessment systems. This study aimed to analyze the effect of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by Kahoot on students' learning outcomes. The study employed a quasi-experimental design with a pretest–posttest control group. The population comprised all Grade 10 students of SMA Negeri 1 Gerung. Two classes were selected using cluster random sampling: an experimental class (n = 30) receiving TGT assisted by Kahoot and a control class (n = 30) receiving conventional instruction. The research instrument was a 25-item multiple-choice learning-outcome test that had been examined for validity and reliability. Learning-outcome data were analyzed using ANCOVA to test differences in final achievement while controlling for initial scores. The results showed that the experimental class had a mean final score of 80.93, whereas the control class had a mean final score of 74.33. The ANCOVA yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. Therefore, it can be concluded that the TGT learning model, assisted by Kahoot, has a significant and effective impact on improving students' learning outcomes and has the potential to serve as an innovative and enjoyable instructional alternative in the classroom.